North Australia Research Unit 1973-1993 - Australian National University. North Australia Research Unit.; Lea, David A. M. (David Alexander Maclure); Wade-Marshall, Deborah (Darwin : North Australia Research Unit, Australian National University, 1993)
History of the establishment and work of the North Australia Research Unit (NARU); lists research projects and themes; staffing; grantees and conferences.
Bibliography: p. 47.
Keywords: Australian National University. -- North Australia Research Unit -- History; Universities and colleges -- Northern Territory -- Darwin -- History; North Australia -- Research -- History; Northern Territory (NT)